ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING - Sri Wulandari; Muh. Nasir Malik; Anas Arfandi; Muhammad Agung; Abdul Muis Mappalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This study aimed to examine the implementation of Creative Problem Solving learning model is better than direct learning model on students’ creative thinking skills in Basic Programming subject in SMKN 1 Soppeng. This research type was experimental research. The nonequivalent control group design was used as experimental design with the samples of 60 students. The data were collected through creative thinking skill test and questionnaire. The collected data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results obtained in this study indicate that the students’ creative thinking skills are better in the implementation of Creative Problem Solving learning model than the direct learning model in Basic Programming subject in SMKN 1 Soppeng. Based on the aforementioned results, it can be concluded that there are differences in student’s creative thinking skills in the implementation of Creative Problem Solving learning model and the implementation of direct learing model in Basic Programming subject in SMKN 1 Soppeng.